Life insurance convexity - Christian Kubitza; Nicolaus Grochola; Helmut Gründl (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
Life insurers sell savings contracts with surrender options, allowing policyholders to prematurely withdraw guaranteed surrender values. Surrender options move toward the money when interest rates rise. Hence, higher interest rates raise surrender rates, as we document for the German life insurance sector. Using a calibrated model, we estimate that surrender options would force insurers to sell up to 2% of their investments during an enduring interest rate rise of 25 bps per annum. The resulting price impact depends on insurers' investment behavior. Forced asset sales are amplified by insurers' long-term investments but mitigated by reducing the guarantees on surrender values.
Keywords: G22; E52; G32; G28; 330; Life Insurance; Liquidity Risk; Interest Rates; Fire Sales; Systemic Risk